Comparative Analysis of the Customer Satisfaction Index and Service Quality Methods in Measuring BPJS Patient Satisfaction at Royal Prima Hospital - Zevanya, Ria Putri; Sari , Christine Ester Novita; MPH, Rafael Crisman; Batubara, Muhammad Rusdi; Nasution, Donni (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2025)
Patient satisfaction is an important indicator for assessing the quality of healthcare services, especially for hospitals serving BPJS patients. By understanding the level of patient satisfaction, hospitals can identify what is performing well and what needs improvement in their services. The objective of this study is to compare two methods, namely the Customer Satisfaction Index (CSI) and Service Quality (Servqual), in measuring BPJS patient satisfaction at Royal Prima Hospital. The CSI method quantitatively measures overall patient satisfaction, while the Servqual method evaluates satisfaction based on four service quality dimensions. This research was conducted through questionnaires distributed to 300 BPJS patients who had received medical services at Royal Prima Hospital. The research findings indicate that the Servqual method produced an average satisfaction score of 2.74, while the CSI method achieved a satisfaction score of 0.69, which falls into the